1995
DOI: 10.1677/joe.0.1440159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclosporine at the hypothalamic-pituitary axis in pituitary-grafted young female rats

Abstract: This work was designed to investigate the effects of cyclosporine on prolactin secretion by an ectopically grafted heterologous pituitary gland, and on the hypothalamic content of norepinephrine, dopamine and serotonin. The administration of cyclosporine prevented the augmentation in plasma prolactin levels which occurred following an ectopic graft of a litter-mate pituitary gland. In contrast, in sham-operated rats, cyclosporine increased prolactin levels on day 8 of treatment. Both pituitary grafting and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…However, in pituitary-grafted animals the reduction was less pronounced thus indicating that, besides the surgery, prolactin modifies NE content in the brain areas studied as shown in previous work from the literature [28]. Acute surgery differentially modifies TAU content in the hypophysiotropic area of the hypothalamus and the median eminence, as was previously shown in the areas studied for dopamine and serotonin metabolisms [4] and for several neuropeptide contents, i.e.…”
Section: Discussionsupporting
confidence: 71%
“…However, in pituitary-grafted animals the reduction was less pronounced thus indicating that, besides the surgery, prolactin modifies NE content in the brain areas studied as shown in previous work from the literature [28]. Acute surgery differentially modifies TAU content in the hypophysiotropic area of the hypothalamus and the median eminence, as was previously shown in the areas studied for dopamine and serotonin metabolisms [4] and for several neuropeptide contents, i.e.…”
Section: Discussionsupporting
confidence: 71%
“…In a previous study we reported the exis tence of an antagonistic interaction between prolactin and cyclosporine in hypothalamic monoamine metabolism [20], similar to that described in lymphocytes [18,19]. In order to further analyze the interrelations between high prolactin levels, cyclosporine and im mune responses, rats made hyperprolactin emic by an ectopic pituitary graft were em ployed.…”
Section: Cyclosporine and Prolactin Interactions In Immune Responsementioning
confidence: 74%
“…Sensitivity was 0.045 ng/ml, using the r-prolactin-RP-3 reference preparation. All samples were mea sured in the same assay to avoid interassay variations [20].…”
Section: Hormone Determinationsmentioning
confidence: 99%
“…(BBB) during acute administration (Fahr, 1993), direct effects on the hypothalamus and the pituitary have been reported (Stephanou et al, 1992;Esquifino et al, 1995;Wera et al, 1995;Chou and Fong, 1999;Ló pez-Calderó n et al, 1999). Thus, CsA might reach the CNS through those brain areas with a weak BBB, like circumventricular organs, subsequently signaling to forebrain structures (Fig.…”
Section: Discussionmentioning
confidence: 99%